The use of digital channels to serve customers in the telecommunications industry - Kiezer, Jason (University of the Witwatersrand, Johannesburg, 2023)
The objective of this paper is to establish and examine the factors that influence customer use of digital channels in the telecommunications industry and the impact of use on customer service. The growth of technological innovation and availability of new systems and technologies allow for improved efficiencies and reduced costs associated with customer care. The telecommunications industry is at the forefront of this technology, promoting self-service through the use of digitals channels across a multitude of platforms with mobile applications, websites, Short Message Service (SMS), Unstructured Supplementary Service Data (USSD) and WhatsApp. This study proposes a new conceptual framework based on Delone and McLean’s (2003) information systems (IS) model by expanding this model to address individual customer use and its impact on customer service. Delone and McLean’s 2003 IS model consists of system quality, information quality, service quality, use and net benefits. The model proposed by this study includes system knowledge, customer innovativeness, service complexity, customer trust, customer satisfaction and customer services. A structured survey questionnaire was utilised for the study, as the focus of the research report is digital channel use by individuals as the unit of analysis. The survey was distributed to 900 users of digital channels in the telecommunications industry who have used various digital channels in the past 24 months to test the conceptual framework. The response rate to the survey 10,6% and 96 responses were analysed using IBM SPSS version 25 and AMOS, using structured equation modelling to validate the model. The results supported Delone and McLean’s (2003) IS model in terms of system quality, information quality, service quality and use. Furthermore, the factors of system knowledge, customer innovativeness, customer trust, customer satisfaction and customer services have a significant impact on customer use. Service complexity was found not to ii be significant in relation to customer use and customer satisfaction. Whilst customer satisfaction is not significant in its influence on customer use. The proposed conceptual model allows leaders in the telecommunications industry to assess key features of digital channels to drive use and thereby, drive cost efficiencies and cost reduction to service and support customers.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business Johannesburg, June 2023
Keywords: Telecommunications; Digital Channels; Self-Service Technologies; Customer Services; Service Complexity; Customer Trust; Customer Trust; System Knowledge; UCTD; SDG-8: Decent work and economic growth